2015
DOI: 10.1001/jamaophthalmol.2015.0457
|View full text |Cite
|
Sign up to set email alerts
|

The Practice Impact of Electronic Health Record System Implementation Within a Large Multispecialty Ophthalmic Practice

Abstract: IMPORTANCE Given the lack of previous reports examining the impact of electronic health record (EHR) system migration in ophthalmology, a study evaluating the practice and economic effect of implementing an EHR into an ophthalmic practice is warranted.OBJECTIVE To examine the clinical and economic impact of EHR system implementation into a large multispecialty ophthalmic practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…In a pre-/post-implementation study in a specialist eye hospital, there was no significant change in patient volume or diagnostic tests usage,87 whereas a similar study in an emergency department reported increased patient processing time, which improved to better than baseline over 10 months. In an outpatient study, physician productivity initially decreased by 20%, but with the corresponding reduced time spent post-clinic reviewing documentation 88.…”
Section: Resultsmentioning
confidence: 87%
“…In a pre-/post-implementation study in a specialist eye hospital, there was no significant change in patient volume or diagnostic tests usage,87 whereas a similar study in an emergency department reported increased patient processing time, which improved to better than baseline over 10 months. In an outpatient study, physician productivity initially decreased by 20%, but with the corresponding reduced time spent post-clinic reviewing documentation 88.…”
Section: Resultsmentioning
confidence: 87%
“…Other studies in academic ophthalmology clinics have found mixed effects from EHR adoption [ 23 – 27 ]. A large study of an entire department reported increased provider non-clinic documentation time with EHR, 6.8 min more per encounter versus paper charting, but with only a 3 % decrease in clinic volume at 2 and 3 years after implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Another study of an academic department consisting of 23 physicians reported no significant change in total patient volume, although glaucoma specialists significantly increased their volume [ 27 ]. However, the authors noted that the department had access to substantial financial and human resources, including a large capital budget for optimization and support staff that was temporarily redistributed during the implementation process.…”
Section: Discussionmentioning
confidence: 99%
“…While EHR use is sometimes thought to lengthen clinical encounters among ophthalmologists and the field of medicine as a whole, studies examining the impact of EHR implementation on ophthalmology practices have demonstrated a mixed impact on patient volume and the time physicians spend in clinic. 5,[22][23][24][25][26][27][28] In our study, the total time that residents and fellows spent per patient encounter did not change with EHR implementation. Average time spent on a patient encounter during a paper chart-based encounter was 11.6 minutes, compared with 11.8 minutes spent on a patient encounter when using the EHR.…”
Section: Discussionmentioning
confidence: 99%